CHILDREN, ADOLESCENTS AND ADULTS IN PRACTICE SPORTS (Fiep Bulletin - online, 2013)
The Practice Sports today has been practised by children, adolescents and even adults are more for an "obligation" than by the pleasure, children are often engaged in practice for a sports influence paternal and maternal, young people feel you are by in fashion and adults by financial need, but as in all cases there are exceptions, of course we have some of those who practice for pleasure, the practice worked well when sports is of fundamental importance for life of the individual, since in addition to work learning the sport is required for training and development of the citizen.
Keywords: Children; Adolescents; practice sports